Thermodynamic Analysis of Supercritical CO2 Power Cycle with Fluidized Bed Coal Combustion - Chenchen Geng; Yingjuan Shao; Wenqi Zhong; Xuejiao Liu (Journal of Combustion)
Closed supercritical carbon dioxide (S-CO2) Brayton cycle is a promising alternative to steam Rankine cycle due to higher cycle efficiency at equivalent turbine inlet conditions, which has been explored to apply to nuclear, solar power, waste heat recovery, and coal-fired power plant. This study establishes 300MW S-CO2 power system based on modified recompression Brayton cycle integrated with coal-fired circulating fluidized bed (CFB) boiler. The influences of two stages split flow on system performance have been investigated in detail. In addition, thermodynamic analysis of critical operating parameters has been carried out, including terminal temperature difference, turbine inlet pressure/temperature, reheat stages, and parameters as well as compressor inlet pressure/temperature. The results show that rational distribution of split ratio to the recompressor (SR1) achieves maximal cycle efficiency where heat capacities of both sides in the low temperature recuperator (LTR) realize an excellent matching. The optimal SR1 decreases in the approximately linear proportion to high pressure turbine (HPT) inlet pressure due to gradually narrowing specific heat differences in the LTR. Secondary split ratio to the economizer of CFB boiler (SR2) can recover moderate flue gas heat caused by narrow temperature range and improve boiler efficiency. Smaller terminal temperature difference corresponds to higher efficiency and brings about larger cost and pressure drops of the recuperators, which probably decrease efficiency conversely. Single reheat improves cycle efficiency by 1.5% under the condition of 600°C/600°C/25Mpa while efficiency improvement for double reheat is less obvious compared to steam Rankine cycle largely due to much lower pressure ratio. Reheat pressure and main compressor (MC) inlet pressure have corresponding optimal values. HPT and low pressure turbine (LPT) inlet temperature both have positive influences on system performance.